HUBUNGAN EFIKASI DIRI DENGAN HASIL BELAJAR SISWA KELAS IV TEMA INDAHNYA KEBERSAMAAN SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU - Nabila Abdul Hakim (STKIP Subang, 2023)
The Association Between Student Learning Outcomes and Self-Efficacy for Class IV Theme 1 Sub-theme 1 SDN Cikaret 1 Bogor City. Primary School Teacher Education Study Program, Pakuan University, Bogor 2022, Faculty of Teacher Training and Education. This study is quantitative and uses a correlational research methodology. In this study, grade IV topic 1 sub-theme 1 Elementary School Cikaret 1 Bogor City students' learning results will be compared to their level of self-efficacy. 120 participants, who were SDN Cikaret 1 fourth graders, made up the study's sample. In this investigation, 56 samples were collected. Between July and August of 2022, this study was conducted. The study's findings demonstrate that there is a relationship between self-efficacy and student learning outcomes to the extent of 25.4%, and the remaining 74.6% is influenced by other factors, according to statistical analysis of the correlation coefficient (rxy) 0.504 and coefficient of determination (r2) 0.254, or 25.4%. Through the regression equation = 33.94 + (0.40X), which states that each increase in one unit of self-efficacy will boost learning outcomes by 0.40, self-efficacy can influence the average student learning outcomes by as much as 25.4%. With a significance level of 0.05, the coefficient tcount 4.265 is calculated to be significantly more significant than ttable 2.045.Based on the explanation above, it can be concluded that there is a relationship between self-efficacy and student learning outcomes for Class IV Theme 1 Sub-theme 1 SDN Cikaret 1 Bogor City, Academic Year 2022/2023.